2007
DOI: 10.1002/anie.200700039
|View full text |Cite
|
Sign up to set email alerts
|

The Renaissance of H/D Exchange

Abstract: The increasing demand for stable isotopically labeled compounds has led to an increased interest in H/D-exchange reactions at carbon centers. Today deuterium-labeled compounds are used as internal standards in mass spectrometry or to help elucidate mechanistic theories. Access to these deuterated compounds takes place significantly more efficiently and more cost effectively by exchange of hydrogen by deuterium in the target molecule than by classical synthesis. This Review will concentrate on the preparative a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
324
1
3

Year Published

2008
2008
2022
2022

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 620 publications
(337 citation statements)
references
References 258 publications
2
324
1
3
Order By: Relevance
“…[2] Organometallic catalysts offer the potential for mild reaction conditions with a high degree of regio-and chemoselectivity. [3,4] Although the study of H/D exchange reactions has tended to concentrate on aromatic [2,3a-i] or aliphatic [2,3a-d,j] compounds, there is an increasing interest in the deuteration of vinylic derivatives.…”
mentioning
confidence: 99%
“…[2] Organometallic catalysts offer the potential for mild reaction conditions with a high degree of regio-and chemoselectivity. [3,4] Although the study of H/D exchange reactions has tended to concentrate on aromatic [2,3a-i] or aliphatic [2,3a-d,j] compounds, there is an increasing interest in the deuteration of vinylic derivatives.…”
mentioning
confidence: 99%
“…Based on these useful properties of C-D bonds, deuterium-labeled organic compounds have traditionally been utilized in various scientific fields, such as the elucidation of reaction mechanisms, investigation of metabolism, microanalysis tracers, etc. [1][2][3][4][5][6] Recently, the delay effects of the metabolism of heavy drugs, which are partially deuterium-labeled original drugs, have been in the spotlight. [7][8][9][10][11][12][13][14][15] Therefore, the development of various preparation methods of deuterium-labeled medicines and synthetic precursors are eagerly awaited in order to contribute to the progress of a wide variety of scientific fields.…”
Section: Deuterium (mentioning
confidence: 99%
“…Besides preparative applications, Ir complexes such as Ir(cod)(acac) or [cp * Ir(PMe 3 )H 3 ]OTf have successfully been applied for hydrogen/deuterium ( H/ D ) exchange reactions, which are important for producing labeled compounds for kinetic and metabolic studies in the pharmaceutical industries [44] . While we do not know of any ' real world ' applications, it has been shown that both selective as well as extensive deuteration are possible, depending on the Ir catalyst and the deuterating agent.…”
Section: References 13mentioning
confidence: 99%